How to retain customers: Understanding the role of trust in live streaming commerce with a socio-technical perspective - Zhang, Mingli; Liu, Yafei; Wang, Yu; Zhao, Lu (Computers in human behavior, 2022)
Live streaming commerce has been the mainstream of e-commerce in recent years. Although live streaming research has gained interest, a holistic model explaining why customers are willing to continuously use such a new sale format remains absent. Drawing on socio-technical system theory, we propose a theoretical model to explore the impact of social and technical enablers on trust and how trust affects users' continuance intention in the live streaming commerce scenario. Empirical results (N = 446) reveal that trust can be enhanced through live interactivity (active control, two-way communication, synchronicity) and technical enablers (visibility, personalization), consequently affects continuance intention. In addition, live streaming genres moderate the impact of different types of trust on continuance intention. Research findings indicate that how trust is formed to generate optimal consequences in live streaming commerce. •Interactivity and IT affordance are essential for trust-building in live streaming.•Trust in different entities is associated with customers' continuance intention.•Trust in streamers is more crucial because it can be transfer to products.•Live streaming genres moderate the impact of trust on continuance intention.